Uncovering mechanisms of rubber biosynthesis in Taraxacum koksaghyz – role of cis‐prenyltransferase‐like 1 protein. (22nd August 2019) - Niephaus, Eva; Müller, Boje; van Deenen, Nicole; Lassowskat, Ines; Bonin, Martin; Finkemeier, Iris; Prüfer, Dirk; Schulze Gronover, Christian
Summary: The Russian dandelion Taraxacum koksaghyz synthesizes considerable amounts of high‐molecular‐weight rubber in its roots. The characterization of factors that participate in natural rubber biosynthesis is fundamental for the establishment of T. koksaghyz as a rubber crop. The cis ‐1, 4‐isoprene polymers are stored in rubber particles. Located at the particle surface, the rubber transferase complex, member of the cis ‐prenyltransferase ( cis PT) enzyme family, catalyzes the elongation of the rubber chains. An active rubber transferase heteromer requires a cis PT subunit (CPT) as well as a CPT‐like subunit (CPTL), of which T. koksaghyz has two homologous forms: TkCPTL1 and TkCPTL2, which potentially associate with the rubber transferase complex. Knockdown of TkCPTL1, which is predominantly expressed in latex, led to abolished poly( cis ‐1, 4‐isoprene) synthesis but unaffected dolichol content, whereas levels of triterpenes and inulin were elevated in roots. Analyses of latex from these TkCPTL1 ‐RNAi plants revealed particles that were similar to native rubber particles regarding their particle size, phospholipid composition, and presence of small rubber particle proteins (SRPPs). We found that the particles encapsulated triterpenes in a phospholipid shell stabilized by SRPPs. Conversely, downregulating the low‐expressed TkCPTL2 showed no altered phenotype, suggesting its protein function is redundant in T. koksaghyz . MS‐based comparison of latex proteomes from TkCPTL1 ‐RNAi plants and T. koksaghyz wild‐types discovered putative factors that convert metabolites in biosynthetic pathways connected to isoprenoids or that synthesize components of the rubber particle shell. Significance Statement: Factors and mechanisms related to the biosynthesis of natural rubber are still not fully elucidated. We show that only TkCPTL1 is necessary for rubber synthesis in the Russian dandelion Taraxacum koksaghyz, while its homolog TkCPTL2 is dispensable for generating poly( cis ‐1, 4‐isoprene). In‐depth characterization of TkCPTL1 ‐depleted plants revealed further insights into the distribution of carbon between rubber, triterpenes, and inulin as well as provided further understanding of rubber particle function in storing latex metabolites.